To What Degree Are the 13 Entrustable Professional Activities Already Incorporated Into Physicians' Performance Schemas for Medical Students?. Issue 4 (8th August 2019) - Colbert-Getz, Jorie M.; Lappe, Katie; Northrup, Michael; Roussel, Danielle
Abstract: Phenomenon: There is an abundance of literature on Entrustable Professional Activities (EPAs) in theory, but there are few studies on the EPAs in practice for undergraduate clinical education. In addition, little is known about the degree to which the EPAs are or are not aligned with physician assessors' performance schemas of the clerkship student. Investigating the degree to which physician assessors' performance schemas are already aligned with the activities described by the EPAs is critical for effective workplace assessment design. Approach: We sampled 1, 032 areas of strength (strength) and areas for improvement (improvement) written evaluation comments by 423 physician assessors for clerkship students' performance in academic years 2014–15 and 2015–16 at the University of Utah School of Medicine. Two researchers independently categorized each comment by EPA and/or coded by non-EPA topic. The proportion of comment types was compared between strength comments and improvement comments with the Wilcoxon Signed-Rank Test. Findings : The most frequently mentioned EPAs in comments were about history gathering/physical exam, differential diagnosis, documentation, presentation, and interprofessional collaboration; few mentioned diagnostic tests, patient handovers, recognition of urgent patient care, and patient safety, and none mentioned orders/prescriptions and informed consent. The most frequent non-EPA topics were about medical knowledge, need to read more, learning attitude, work ethic, professionalism/maturity, and receptiveness to feedback. The proportion of comments aligned with an EPA only, a non-EPA topic only, or both an EPA and non-EPA topic was significantly different for clerkship students' strength compared to improvement. Insights: Physician assessors' performance schemas for clerkship students were aligned with EPAs to varying degrees depending on the specific EPA and whether describing strength or improvement. Of interest, the frequently mentioned non-EPA comments represented some of the competencies that contribute to effectively performing particular EPAs and are Accreditation Council for Graduate Medical Education (ACGME) core competencies (e.g., medical knowledge, professionalism), used in residency programs. Because physician assessors for undergraduate medical education often also participate in graduate medical education, the frequency of non-EPA topics aligned to ACGME competencies may suggest influence of graduate medical education evaluative frameworks on performance schemas for clerkship students; this could be important when considering implementation of EPAs in undergraduate medical education.